Análisis de los factores socio laborales que inciden en la rotación del personal en la generación millenials e impacto de este fenómeno en los procesos estructurales de las corporaciones modernas (2020)
This research study is carried out in order to recognize the factors in terms of job development that influence the Millennial generation in terms of staff turnover, in addition to recognizing the causes that urge organizational change in the current job market. Many of the young people who are part of this generation last a short time in their workplace because their expectations exceed the visions of job development in that company, in other words, they are not inflexible and seek to generate a high impact on the organization through new development bets, they are enterprising, innate, impulsive, proactive and highly creative.If companies are currently unable to define a management scheme that promotes labor absorption and integration policies oriented towards the Millennial generation, They will not respond efficiently to the new challenges of the labor market, understanding this as the means through which all the workers' competencies are developed and provide the means to offer a product or customer service of full quality. Current organizations must realize the new reality and for this they must stimulate the integration of new talents, the association positions of the human talent department must be more flexible in search of elements that create better scenarios for labor flexibility, better spaces for labor autonomy.